2017
DOI: 10.3892/mmr.2017.8118
|View full text |Cite
|
Sign up to set email alerts
|

KIF9‑AS1, LINC01272 and DIO3OS lncRNAs as novel biomarkers for inflammatory bowel disease

Abstract: Long non-coding RNAs (lncRNAs) are a novel group of non-coding RNAs that are associated with inflammation and tumorigenesis. At present, the diagnostic efficacy of lncRNAs in inflammatory bowel disease (IBD) is unclear. The present study aimed to identify lncRNAs that may be used as potential biomarkers for IBD. The mRNA expression levels of various lncRNAs (KIF9-AS1, LINC01272 and DIO3OS) were detected in tissue and plasma samples from patients with IBD by reverse transcription-quantitative polymerase chain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 35 publications
0
50
0
Order By: Relevance
“…LINC01272 has been shown to be associated with a myeloid proinflammatory signature in Crohn's disease and was significantly upregulated in inflammatory bowel disease. 38,39 Moreover, LINC01272 is closely related to the survival time of lung squamous cell carcinoma. 40 Nevertheless, the target genes are unidentified and the mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01272 has been shown to be associated with a myeloid proinflammatory signature in Crohn's disease and was significantly upregulated in inflammatory bowel disease. 38,39 Moreover, LINC01272 is closely related to the survival time of lung squamous cell carcinoma. 40 Nevertheless, the target genes are unidentified and the mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, determining the involvement of cancer-specific lncRNAs may prove beneficial for identifying novel targets for anticancer treatment. Wang et al ( 11 ) suggested that lncRNA KIF9-AS1 may belong to a novel group of non-coding RNAs, which are associated with inflammation and tumorigenesis ( 12 ). Thus, the present study aimed to determine the expression levels of KIF9-AS1 in NPC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lncRNA PICART1 was reported to inhibit the progression of non-small cell lung cancer cells through inactivation of the AKT1 signaling pathway ( 10 ), and lncRNA XIST is associated with a poor prognosis and promotes a malignant phenotype in osteosarcoma ( 11 ). Recently, KIF9-AS1 was also reported to be a biomarker for inflammatory bowel disease ( 12 ). However, to the best of our knowledge, there are currently no relevant studies regarding the role of KIF9-AS1 in NPC.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a few other studies have analyzed smaller datasets and observed changes in IBD speci c ncRNAs, i.e. LINC01272 10 , DIO3OS 11 , and KIF9-AS 11 using RT-PCR in intestinal tissues and plasma samples in IBD. In particular, the expression of these ncRNAs was greater in IBD patients when compared to controls 11 .…”
Section: Introductionmentioning
confidence: 99%
“…LINC01272 10 , DIO3OS 11 , and KIF9-AS 11 using RT-PCR in intestinal tissues and plasma samples in IBD. In particular, the expression of these ncRNAs was greater in IBD patients when compared to controls 11 . However, none of these studies explored whether the ncRNAs expression are speci c to tissue types, CD disease behaviors, disease location or disease in ammation.…”
Section: Introductionmentioning
confidence: 99%